2015
DOI: 10.1080/00224499.2014.996280
|View full text |Cite
|
Sign up to set email alerts
|

Conundrum of Sexual Decision Making in Marital Relationships: Safer-Sex Knowledge, Behavior, and Attitudes of Married Women in Zambia

Abstract: Recent research suggests that Zambian women face an increasing risk of contracting human immunodeficiency virus (HIV) within marital relationships. Married women's perceived ability to negotiate safer sex or adopt self-efficacy practices is recognized as critical in preventing new infections within marriage. Yet women's self-efficacy practices, such as requesting condom use or refusing sex within marriage, are influenced by individual and context-specific factors. Using the 2007 Zambia Demographic and Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…There were four questions related to HIV transmission beliefs: whether respondents believe that 1) HIV can be spread through witchcraft and other supernatural means; 2) HIV can be spread through sharing food with a person with HIV; 3) HIV can be spread through mosquito bites; 4) and, a healthy-looking person cannot be infected with HIV. Previous studies [ 3 6 ] have concluded that endorsing any form and/or number of misconception about HIV transmission is associated with risky sexual behaviours. Also, governments and NGOs in Malawi have put much effort into eliminating misconceptions about HIV transmission [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were four questions related to HIV transmission beliefs: whether respondents believe that 1) HIV can be spread through witchcraft and other supernatural means; 2) HIV can be spread through sharing food with a person with HIV; 3) HIV can be spread through mosquito bites; 4) and, a healthy-looking person cannot be infected with HIV. Previous studies [ 3 6 ] have concluded that endorsing any form and/or number of misconception about HIV transmission is associated with risky sexual behaviours. Also, governments and NGOs in Malawi have put much effort into eliminating misconceptions about HIV transmission [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite major efforts at behaviour change, myths and misconceptions about HIV transmission remain an important influence on risky sexual behaviours [ 3 6 ]. Subsequently, the behavioural change model is limited in capturing the influence of myths and misconceptions to inform clinical or scientific understanding of the ways in which HIV is transmitted or prevented [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Misconceptions about HIV/AIDS could usually be associated with different risky behaviours that might lead to getting infected with HIV [10] [14]. Misconception has the potential of preventing people from taking necessary steps aimed at preventing HIV infection [26].…”
Section: Resultsmentioning
confidence: 99%
“…This is worrisome since misconceptions of these types are associated with behaviours that are predisposed to HIV infection [14]. Correct knowledge about HIV is very crucial in controlling the spread of the infection [15].…”
Section: Introductionmentioning
confidence: 99%